El control interno contable y fiscal como medida para contribuir a la maximizacion de los resultados financieros de los negocios (The accounting and fiscal internal control as a measure to contribute to the increasing of the business financial results) - Hernández Campos, Alfonso (UANL. Facultad de Contaduría Pública y Administración, 2016)
Abstract. The main purpose of this article is to show the importance of accounting and fiscal internal controls to contribute to the compliance of outlined objectives in the private and public organizations, through an efficient and effective management of resources with which organizations count. In addition, this article will address the difficulties of the implementation derived from of its incipient requirement, also of its ignorance of usefulness but above all for the general idea of the possible costs that usually should spend in its implementation. To accomplish the above, it analyze the relevant aspects of the control as a part of the administrative process, from there address its classification as an internal control: accounting and fiscal. Also it address certain innovative methodologies that are useful as a tools of implementation of internal controls such as SWOT analysis, the methodology of 5 Whys, the correlation index and the Pareto diagram, which have been useful in other fields like Engineering and we can use them with success in the Accountant field.